Dakwah Bil Hal by the Onsight Foundation to Address the Clean Water Crisis - Nurokhman, Firmansyah Nugroho; Triatmo, Agus Wahyu; Mahardika, Mei Candra; Saidun, Muhammad; Suryono, Joko (STAI Publisistik Thawalib Jakarta, 2025)
The 1000 Water Sources Expedition Program by the Onsight Foundation in Ngelo, Wonogiri, utilizes vertical cave water sources to overcome a decades-long clean water crisis. This study aims to examine the implementation of Dakwah Bil Halthrough the 1000 Water Sources Expedition Program in enhancing access to clean water. Employing a descriptive qualitative approach, data collection involved in-depth interviews, with data analysis encompassing data reduction, presentation, and verification. The findings reveal that the 1000 Water Sources Expedition Program in Ngelo Hamlet progressed through pre-implementation, implementation, and post-implementation phases, facilitated by participatory communication that actively involved the community. Rope access and speleological technologies were employed to access water sources in vertical caves, providing a stable, year-round supply of clean water. The program not only fulfills basic water needs but also reinforces religious, social, and economic activities. The community participates in water management and MSME empowerment, supported by socio-religious activities. The program successfully enhances solidarity, religious awareness, and overall community independence. The study concludes that water endowment (wakaf) serves as an effective strategy for dakwah and empowerment, resolving clean water access issues, fostering religiosity and cooperation, and improving the welfare of rural communities.